The Role of Motivational Climate in Predicting Emotional Intelligence and Self-Concept Among Elementary School Students - Vinna Shovina; Inggri Anggraeni Setiawati; Xinbi Nasywabilla Az-Zahra; Rahmah Nurusoimah; Anistya Rengganis (MIREJ: Multidisciplinary Innovation Research Journal, 2026)
This study examined the relationship between motivational climate (task-involving and ego-involving climate), emotional intelligence, and self-concept in 280 students in grades 5–6 of public elementary schools in Cirebon City, West Java, using a cross-sectional descriptive-explanatory design and PLS-SEM analysis (SmartPLS 3). The results showed that task-involving climate had a positive and significant effect on ego-involving climate, emotional intelligence, and self-concept, as well as emotional intelligence had a positive and significant effect on self-concept; On the other hand, ego-involving climate had no significant effect on these two variables. In addition to extending the application of Achievement Goal Theory to the general learning context in elementary schools and giving teachers a useful foundation for creating a classroom environment that prioritizes effort and learning processes, these findings confirm task-involving climate as the primary factor influencing students' emotional intelligence and self-concept.